Mortality study of workers in the man-made mineral fiber production industry in the United Kingdom. - Gardner, Martin J.; Winter, Paul D.; Pannett, Brian; Simpson, M. J.; Hamilton, C.; Acheson, E. D. (Scandinavian Journal of Work, Environment & Health, 1986)
The workforces of two factories in the United Kingdom have been followed up to the end of 1984 as part of the collaborative European study of the health of workers in the man-made mineral fiber industry. In the cohort from an English glass-wool plant there was no suggestion of any excess mortality compared to national or local rates, except for lung cancer among men in comparison to the national level. However, the data indicate that the workers were largely local persons by place of birth, occupation, and death, and they therefore suggest that the national comparison was inappropriate. Lung cancer mortality showed little relationship to length of employment, duration of time since first exposure, occupational classification, or level of exposure. In the cohort from a continuous-filament plant in Northern Ireland no excess mortality from cancer was found. There were, however, raised death rates from violent causes and cardiovascular disease, but these rates were not exceptional for the area of the country in which the factory was located. No deaths from mesothelioma were reported in either cohort.